1982
DOI: 10.1159/000166588
|View full text |Cite
|
Sign up to set email alerts
|

Medullary Sponge Kidney and Hyperparathyroidism -a Puzzling Association

Abstract: 28 adult patients with radiological evidence of medullary sponge kidney (MSK) were studied. Hypercal-cemia and increased serum parathyroid hormone (PTH) values were found in 10 patients (36%). In 7 of them, parathyroid surgery was performed: a single adenoma was found in 6 cases and multiple-gland hyperplasia in 1 case. After surgery, 3 patients had normalization of calcium metabolism; 4 patients had persistence of hypercalciuria with progressive increase in serum PTH values (and recurrence of the adenoma in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…In our case, our patient had recurrent renal stones, urinary tract infection, hypokalemia, morning urine pH > 5.5, and acidosis, which were consistent with MSK and dRTA. Hyperparathyroidism is also reportedly associated with a few patients with MSK [ 3 , 6 ], but the exact association between the two diseases is still controversial as both diseases can manifest as kidney stones and excessive urinary calcium excretion. Some scholars believe that hyperparathyroidism is a cause of MSK and triggers nephrolithiasis in these patients [ 6 ], while others believe that MSK could be the primary factor, and parathyroid adenoma might occur secondary to long-term negative calcium balance caused by high urinary calcium [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, our patient had recurrent renal stones, urinary tract infection, hypokalemia, morning urine pH > 5.5, and acidosis, which were consistent with MSK and dRTA. Hyperparathyroidism is also reportedly associated with a few patients with MSK [ 3 , 6 ], but the exact association between the two diseases is still controversial as both diseases can manifest as kidney stones and excessive urinary calcium excretion. Some scholars believe that hyperparathyroidism is a cause of MSK and triggers nephrolithiasis in these patients [ 6 ], while others believe that MSK could be the primary factor, and parathyroid adenoma might occur secondary to long-term negative calcium balance caused by high urinary calcium [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some speculated that variants of GDNF and RET genes, which play a key role in kidney and urinary tract development, maybe reasonable candidates for MSK. Hyperparathyroidism is observed in a few patients with MSK, but the exact pathogenesis of this association is unknown [ 3 , 6 ]. In the current study, we present a case of MSK accompanied with tertiary hyperparathyroidism in whom we analyzed the GDNF and RET gene variations, which contributes to further understanding of the pathogenesis of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although serum calcium levels were well below those indicative of hyperparathyroidism in all our MSK subjects, the opposing serum concentration calcium and phosphate gradi-ents in the different groupings of relatives and the marginally higher PTH levels observed in the probands bring to mind the old notion that MSK patients may have hyperparathyroidism. 11,12 The reasons for such an association are not known. It has been suggested that hyperparathyroidism causes MSK and also triggers stone formation in these patients, 12 but hypercalciuria, nephrocalcinosis, and renal stones clearly precede the onset of hyperparathyroidism by many years in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The reasons for such an association are not known. It has been suggested that hyperparathyroidism causes MSK and also triggers stone formation in these patients, 12 but hypercalciuria, nephrocalcinosis, and renal stones clearly precede the onset of hyperparathyroidism by many years in most patients. It has also been claimed that renal hypercalciuria triggers parathyroid gland stimulation, leading to hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Maschio et al [29] have recently provided evidence that precalyceal canalicular ectasias can develop as a conse quence of prolonged hypercalciuria. Our data do not support this contention; however, 2 patients with medul lary sponge kidneys had undergone a series of IVPs over a period of time ranging from 4 to 15 years, and in both cases the typeiai radiological signs were present from the time of the first investigation on.…”
Section: Discussionmentioning
confidence: 99%